Tracéologie du bois d’époque médiévale - Manuel Porcheron (Revue Archéologique du Centre de la France)
Understanding tool markings (traceology) on wood enables an analysis of the technical gestures of woodcutters and carpenters, which in turn allows for the identification of the physical movements made by the craftspeople during the manufacturing process. This article aims to lay the foundations for a methodology to analyse tool markings (traceology) from the Middle Ages through the comparison of archaeological and experimental markings. Such an analysis will lead to improved knowledge about woodcutters and carpenters from the era, as well as a deeper understanding of their gestures and techniques. Thus, revealing details about the tools they used, their levels of expertise and universal techniques. Across scientific study, the clarification of terms allows a precise and shared understanding of concepts and words. This holds true for the categorisation of physical markings on wood, for example: cupules/cup markings, torn grain, cross cut markings, gouging, chipping and so on. Such a typology makes it possible to identify characteristics that can be generalized and then used to establish a database of recorded makings according to their different, and shared, characteristics. When creating such a database it is necessary to examine how researchers record the markings on both the archaeological and the experimental sites. In addition to discussion around the methodology and findings, a methodology specific to the experimental sites is outlined. In order to make the overall methodology more tangible, examples of the links between the archaeological and the experimental data are presented.